Medicare Imaging Demonstration Final Evaluation Report to Congress - Timbie, Justin W. (RAND Corporation, 2014)
In 2011, the Medicare Imaging Demonstration from the Centers for Medicare & Medicaid Services began testing whether exposing ordering clinicians to appropriateness guidelines for advanced imaging would reduce ordering inappropriate images. Small changes in ordering patterns were noted, but decision support systems were unable to assign appropriateness ratings to many orders, limiting the potential effectiveness of decision support.